Natural regeneration on land degraded by coal mining in a tropical climate: Lessons for ecological restoration from Indonesia. (27th September 2018) - Novianti, Vivi; Marrs, Rob H.; Choesin, Devi N.; Iskandar, Djoko T.; Suprayogo, Didik
Abstract: There are few examples of primary succession from tropical conditions, especially on land degraded by human activity, for example, mine wastes. Such studies would assist in informing ecological restoration of these degraded sites. Here, a chronosequence approach was used to investigate early‐stage primary succession on overburden spoil wastes derived from coal mining in a tropical climate over a 64‐month period. Plant species composition and several microclimatic and spoil physicochemical and microbial properties were measured, and responses analysed using regression and multivariate (nonmetric multidimensional scaling) analyses. A clear primary successional process was described showing that vegetation cover and species richness generally increased through time with a successional pathway from graminoids and herbs as the early dominants, shrubs in midsuccession, and trees in the later‐successional stages. Two important differences were noted between our results and primary successions elsewhere; a lower abundance of nitrogen‐fixing species and the colonization by some late‐successional shrubs and trees at the start. During the succession, aggregate stability and organic matter (total C) increased—whereas electrical conductivity and some potentially toxic elements (Al, B) decreased. The constant high spoil moisture content appears to be an important determinant of vegetation development during primary succession and may be a factor in the rapid pace of succession detected here. The lessons for ecological restoration for coal overburden spoil under tropical conditions are that succession can proceed relatively rapidly.